Propuesta de un programa de enseñanza de halterofilia en edades de 10 a 12 años para los estudiantes de la escuela de educación básica Dr. Alfredo Diezcanseco de la ciudad de Machala periodo lectivo 2013-2014. - Freire Reina, Víctor Manuel (2015)
This thesis research on the theme PROPOSED PROGRAM HALTEROFILIA TEACHING IN AGES 10 TO 12 YEARS FOR STUDENTS OF BASIC EDUCATION SCHOOL OF DR. ALFREDO Diezcanseco CITY MACHALA LECTIVO PERIOD 2013-2014, it is divided into five chapters as follows: In chapter one has the problem definition, objective which will help us to find the information relevant and necessary to develop this research work in relation to the teaching program of weightlifting aged 10-12 years. In chapter two the theoretical aspect in support of the research which will address the issues of weightlifting aged 10-12 years, as well as the teaching and history of the sport. In chapter three corresponds to the methodology used to develop this research. In chapter four we have the presentation of research results presentation of information in chart and graph, analysis and interpretation. In chapter five we show the proposed intervention that will solve the problem investigated in the same learning program that will be applied to students ages 10 to 12 years will apply